Kenya Economic Update, October 2018 : In Search of Fiscal Space - World Bank Group (Washington, DC: World Bank, 2018)
The Kenyan Economy is on a rebound in 2018. Reflecting improved rains, better business sentiment and easing of political uncertainty, economic activity is rebounding after the slowdown in activity in 2017. According to official statistics, the economy expanded from 4.7 percent in H1 of 2017 to 6.0 percent in H1 of 2018 supported by improved harvest in agriculture, steady recovery in industrial activity, and still robust performance in the services sector. As a result, real GDP growth is projected to reach 5.7 percent in 2018, an upward revision of 0.2 percentage points from the April 2018 Economic Update. Growth in private consumption and investment are driving the rebound. Private consumption picked up in 2018 fueled by rising household incomes from improved agricultural harvests, lower food prices, and strong remittance inflows. A recovery in private sector investment activity is also underway, partly reflected in increased imports of raw materials and chemicals and more positive investor sentiment with the Purchasing Managers’ Index remaining in expansionary territory (above the 50- mark) for H1 2018 at 55.1 points compared to 49.7 points over the same period in 2017. The recovery in private sector activity (consumption and investment) is expected to off-set potential drag in growth due to unwinding of fiscal stimulusat a time when fiscal consolidation is gathering momentum. Net exports continued to weigh on growth owing to faster expansion in imports relative to Kenya’s exports. There are three key policy recommendations from this analysis. First, the government could consider expanding direct cash transfer programs. Cash transfer programs are well-targeted so that a large fraction of the benefits are captured by the poor. These programs could further be expanded in order to increase their poverty-reducing effect. However, this will require enhancing revenue mobilization for the coverage to increase significantly. Second, exemptions granted within Kenya’s VAT regime appear to benefit the poor only marginally. The variation in consumption shares of exempt and zero-rated items across the welfare distribution is small. A review of the VAT law might help remove exemptions and increase revenue that could then be spent in well-targeted and progressive cash transfer programs. However, a more detailed follow-up analysis of exemptions and zero-rates would be necessary to determine item-level incidence. Third and finally, shifting public resources from higher-level health facilities to lower-level facilities is likely to benefit the poor. Conditional on uptake, public health spending on outpatient care is pro-poor while the associated user fees and over the counter purchases are regressive. The results suggest that redirecting spending from higher-level public health facilities to primary care facilities has the potential to benefit the poor and might increase access.